Active hydrogenation Rh nanocatalysts protected by new self-assembled supramolecular complexes of cyclodextrins and surfactants in water. Issue 109 (14th November 2016) - Thanh Chau, Nguyet Trang; Menuel, Stéphane; Colombel-Rouen, Sophie; Guerrero, Miguel; Monflier, Eric; Philippot, Karine; Denicourt-Nowicki, Audrey; Roucoux, Alain
Abstract : New supramolecular assemblies as protective agents of rhodium(0) nanoparticles for hydrogenation of various substrates in water. Abstract : The stability of inclusion complexes between randomly methylated β-cyclodextrin (RaMeCD) or its leucine-grafted analogue (RaMeCDLeu) with two hydroxylated ammonium surfactants was investigated. The binding isotherms and complexation constants were measured using the Isothermal Titration Calorimetry (ITC) technique. These host–guest inclusion complexes were used as protective agents during the formation of rhodium(0) nanoparticles by chemical reduction of rhodium trichloride in water. The amount of protective agent was adjusted in order to ensure both stability and reactivity of the rhodium nanocatalysts under the catalytic conditions. The size and dispersion of air-stable and water-soluble rhodium suspensions were determined by Transmission Electron Microscopy (TEM) analyses. These spherical nanoparticles, with sizes between 1.20 to 1.50 nm according to the nature of inclusion complexes, were evaluated in the biphasic hydrogenation of various reducible compounds (olefins, linear or aromatic ketones), showing promising results in terms of activity and selectivity.